Viral Determinants and Vector Competence of Zika Virus Transmission - Tham, Hong-Wai; Balasubramaniam, Vinod; Ooi, Man K.; Chew, Miaw-Fang (Frontiers in Microbiology, 2018)
Zika virus has emerged as a new global health threat. Since its first discovery in Zika forest in Uganda, this virus has been isolated from several mosquito species, including Aedes aegypti and Aedes albopictus. The geographical distribution of these mosquito species across tropical and subtropical regions has led to several outbreaks, including the recent pandemic in Brazil, followed by the Pacific islands and other areas of North and South America. This has gained attention of the scientific community to elucidate the epidemiology and transmission of Zika virus. Despite its strong attention on clinical aspects for healthcare professionals, the relationships between Zika virus and its principal vectors, Ae. aegypti and Ae. albopictus, have not gained substantial interest in the scientific research community. As such, this review aims to summarize the current knowledge on Zika virus tropism and some important mechanisms which may be employed by the virus for effective strategies on viral survival in mosquitoes. In addition, this review identifies the areas of research that should be placed attention to, for which to be exploited for novel mosquito control strategies.